Analysis Customer Satisfaction of Repurchase Intention in Gold Purchase Field for Investment During Pandemic COVID-19 - Diandra Ariani Syafitri (Jurnal Indonesia Sosial Sains, 2022)
The whole world is hit by the respiratory and airborne disease, or COVID-19 outbreak. The beginning of the COVID-19 pandemic began in Wuhan, China in December 2019. This study aims to analyze a person's satisfaction in repurchasing eman which can be used as an investment during the pandemic. By analyzing buyer satisfaction, products, services, and repurchase prices in purchasing gold for investment during the pandemic. The research technique used is a quantitative technique, carried out by distributing questionnaires to 110 gold buying and selling actors who have made gold buying and selling transactions from one time during the pandemic. The research was conducted using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) alternative with the Smart-PLS 3.3.3 program. The results obtained indicate that there are: (1) There is a significant relationship and influence on consumer satisfaction with repurchase (Repurchase Intention) (2) While Product, Service, and Price Interest on Repurchase Intention is not significant